Health improvements for a healthy Shanghai rising: Comment on "Shanghai Rising: health improvements as measured by avoidable mortality since 2000" - Ren, Yuan (Int J Health Policy Manag, 2015)
The commentator suggests that it is necessary to extend the classical connotation of global city which focuses much on the functions of controlling global capital and production. Global city should also include the dimensions of the leading role and capacity on health improvements and well-being promotion. The commentator agrees with authors’ assessments about Shanghai’s substantial progress on health services and health system reform, however, we should pay much attention to the significant inequality of health services between central city and outskirt, and between local residents and non-hukou migrants. The commentator also suggests that future researches could study the successful experiences of Avoidable Mortality (AM) decline and also disease specific AM decline in main global cities, in order to make more effective policy implications and social schemes recommendations for health improvements in Shanghai and in other cities.